1-A-D-25. Ictal limb posturing differs between seizures arising from temporal lobe and supplementary motor area: A video-EEG study. Issue 6 (June 2015) - Sato, Kei; Bayasgalan, Borgil; Matsumoto, Riki; Kobayashi, Katsuya; Fumuro, Tomoyuki; Sakurai, Takeyo; Shimotake, Akihiro; Takahashi, Ryosuke; Ikeda, Akio
Abstract : Focal seizures arising from the temporal lobe (TL seizures) resemble those from supplementary motor area (SMA) with resepct to ictal dystonic and/or tonic posturing. The aim of this study is to clarify the symptomatic difference and then underlying mechanism between TL- and SMA seizures by careful observation of ictal posturing. Among patients with partial epilepsy who performed long-term video-EEG monitoring from 1992 to 2014, we employed 13 patients with TL seizures showing discrete dystonic posture and 12 patients with SMA seizures showing clear abnormal tonic posture. We reviewed the posturing and the movement direction of the shoulder, elbow and wrist joints of both seizures. As the results, shoulder adduction was observed significantly more in TL seizures than SMA seizures ( p  < 0.05). Elbow supination was also observed more in TL seizures than SMA seizures (marginal trend p  < 0.1). The movement patterns in the shoulder and elbow could differentiate TL seizures from SMA seizures. Taken together into account previous ictal SPECT studies which showed different site of hyperperfusion in basal ganglia between TL- SMA seizures, our results suggest the different degree of involvement in the basal ganglia between TL and SMA seizures.